Depression and its associated factors among textile factory workers at the Almeda textile factory, North Ethiopia - Tesfaye Derbie Begashaw; Fantahun Andualem (Frontiers Media S.A., 2024)
BackgroundDepression is becoming a significant burden and a potential cause of disability worldwide. According to a World Health Organization (WHO) study conducted in both developed and developing countries, the prevalence of depression is 10.4%. There are differences in the prevalence of depression among the population based on a number of variables, including concomitant medical problems, substance abuse, employment environment, and demographics. The purpose of this study was to evaluate the prevalence of depression and its associated risk factors among textile industrial workers.MethodsA cross-sectional study was conducted on 409 workers from the Almeda Textile Factory in Adwa from May to June 2020. The outcome variable was depression, assessed using the Patient Health Questionnaire-9 (PHQ-9). Variables with p-values of <0.25 in the bivariate analysis were included in the multivariate analysis. An adjusted odds ratio with a 95% confidence interval was computed. Statistical significance was determined at a p-value of <0.05.ResultsThe total prevalence of depression at a PHQ-9 cutoff score of 10, PHQ-9(10+), was 24.4%. At a cutoff score of 5, PHQ-9(5+) was 51.1%. In the multivariate analysis, low social support, working rotating day and night shifts, and having a physical injury at the workplace were significantly associated with depression at both PHQ-9(5+) and PHQ-9(10+). In addition, advanced age of 45 years and above and being diagnosed with chronic medical disease were significantly associated with depression at PHQ-9(10+) (p < 0.05).ConclusionThe prevalence of depression varied based on the PHQ-9 cutoff score, and it is high at both PHQ-9(5+) and PHQ-9(10+). Low social support, working rotating day and night shifts, physical injury at the workplace, advanced age, and chronic medical disease were significantly associated with depression. Our findings suggest that the workers at the Almeda Textile Factory should be screened and managed accordingly.